Independent erosion of conserved transcription factor binding sites points to shared hindlimb, vision and external testes loss in different mammals. Issue 18 (23rd August 2018) - Berger, Mark J; Wenger, Aaron M; Guturu, Harendra; Bejerano, Gill
Abstract: Genetic variation in cis -regulatory elements is thought to be a major driving force in morphological and physiological changes. However, identifying transcription factor binding events that code for complex traits remains a challenge, motivating novel means of detecting putatively important binding events. Using a curated set of 1154 high-quality transcription factor motifs, we demonstrate that independently eroded binding sites are enriched for independently lost traits in three distinct pairs of placental mammals. We show that these independently eroded events pinpoint the loss of hindlimbs in dolphin and manatee, degradation of vision in naked mole-rat and star-nosed mole, and the loss of external testes in white rhinoceros and Weddell seal. We additionally show that our method may also be utilized with more than two species. Our study exhibits a novel methodology to detect cis- regulatory mutations which help explain a portion of the molecular mechanism underlying complex trait formation and loss.